STRATEGI KOMUNIKASI KELOMPOK PADA IKATAN DUTA BAHASA DALAM PROGRAM KERJA “PERLU GALAKSIS” - YENI KARTIKA (UNIVED PRESS, Universitas Dehasen Bengkulu, 2021)
The purpose of this research is to know and describe the group communication strategy that is carried out by the ambassadors of language ties in the work program which is